2018
DOI: 10.18502/kls.v4i4.2281
|View full text |Cite
|
Sign up to set email alerts
|

Role of Social Support in Breastfeeding for Adolescent Mothers

Abstract: Breastfeeding plays an important role in a baby's life and is especially important for babies with a low birthweight (LBW), which is the highest cause of death in neonates.In 2012, the number of adolescent mothers with a higher risk of delivering LBW babies increased as reported by BKKBN. This study aimed to identify factors affecting adolescent mothers' breastfeeding behaviors in Sidotopo, Surabaya, Indonesia through an observational, descriptive, and qualitative approach with a cross-sectional design. Seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…In line with the results of this study, findings of other research corroborated such participants’ needs for assurance and respect. 26 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…In line with the results of this study, findings of other research corroborated such participants’ needs for assurance and respect. 26 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, efforts to encourage EBF need to address social support to those mothers, who are illiterate or only had less than school-level education. They should get support from their parents or family members which may facilitate to practice of EBF positively, but studies elsewhere show that having inadequate information negatively affects EBF in Indonesia, 39 and Cyprus. 40 It also suggested that emotional, and informational supports were perceived as effective support for breastfeeding initiation and practice of EBF.…”
Section: Determinants Of Ebf Practicesmentioning
confidence: 99%
“…Menurut beberapa anggota keluarga mungkin kurang memiliki pengetahuan tentang menyusui, atau mereka mungkin juga memberikan dukungan yang tidak sesuai dengan tenaga kesehatan, seperti saran dari nenek yang menganjurkan pemberian makanan selain ASI (Khonsung et al 2020). Informasi dari anggota keluarga yang kurang tepat pada ibu usia di bawah 20 tahun yang belum memiliki kesiapan dan pengetahuan tentang memberikan ASI dapat menyebabkan motivasi yang rendah pada ibu dalam memberikan ASI eksklusif (Palupi & Devy, 2018).…”
Section: Pembahasan 1 Faktor Pengetahuan Dengan Pemberian Asi Eksklus...unclassified
“…Ibu usia di bawah 20 tahun yang tinggal bersama anggota keluarga yang lain atau keluarga besar (extended family) dapat memperoleh berbagai bentuk dukungan dari anggota keluarga lainnya untuk memberikan ASI eksklusif, seperti ibu kandung, ayah, mertua, dan kakak perempuan dari ibu usia di bawah 20 tahun. Menurut ibu, keluarga juga mendukung pemberian ASI adalah ibu / mertua dan suami, selain itu juga mendapat dukungan dari bibi dan nenek mereka (Palupi & Devy, 2018). Dukungan emosional yang selalu diberikan oleh keluarga antara lain: perhatian, kepedulian, dan kata-kata penyemangat untuk memberikan ASI.…”
Section: Faktor Dukungan Dengan Pemberian Asi Eksklusif Pada Ibu Usia...unclassified
See 1 more Smart Citation